C-glycosides of dodecanoic acid: new capping/reducing agents for glyconanoparticle synthesis - Ramana, C. V.; Durugkar, Kulbhushan A.; Puranik, Vedavati G.; Narute, Sachin B.; Bhagavatula L. V. Prasad (Tetrahedron Letters, 2008)
A concise synthesis of 12-C-glycosylated dodecanoic acids employing an olefin cross-metathesis reaction is developed. Examination of these acids as capping agents for the synthesis of metal nanoparticles reveals that they do not cap the Co-metal nanoparticles synthesized in aqueous phase, but that two of them can reduce and cap the Ag nanoparticles in water without any aggregation. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: C-Glycosides; Cross metathesis; glyconanoparticles; Grubbs' catalyst; silver nanoparticles

Click synthesis of isomeric compounds for assessing the efficiency of the bifurcated Br center dot center dot center dot NO2 synthon - Ramana, C. V.; Chatterjee, Soumitra; Durugkar, Kulbhushan A.; Gonnade, Rajesh G. (Crystengcomm, 2009)
We report herein the extention of the azide-alkyne ``click reaction'' to crystal engineering and synthesize a collection of isomeric compounds with modular positioning of Br and NO2 on a tricyclic template and crystal structural analyses of the derived isomers. It is quite remarkable to notice that none of the isomers displayed the bifurcated three-center NO2 center dot center dot center dot Br supramolecular synthon in their crystal structures

Cu(I)-promoted one-pot `SNAr-click reaction' of fluoronitrobenzenes - Durugkar, Kulbhushan A.; Gonnade, Rajesh G.; Ramana, C. V. (Tetrahedron, 2009)
A one-pot two-step sequence involving a nucleophilic aromatic substitution (SNAF) of activated fluorobenzenes with azide nucleophile and in situ Huisgen cycloaddition of the resulting aryl azides with alkynes has been developed for a rapid access to 1,4-substituted triazoles. Control experiments revealed that both the steps are catalyzed by Cu(I) and also the course of reaction as SNAr followed by [3+2]-cycloaddition. (C) 2009 Elsevier Ltd. All rights reserved.